SPRED1 germline mutations caused a neurofibromatosis type 1 overlapping phenotype. Issue 7 (14th April 2009) - Pasmant, E; Sabbagh, A; Hanna, N; Masliah-Planchon, J; Jolly, E; Goussard, P; Ballerini, P; Cartault, F; Barbarot, S; Landman-Parker, J; Soufir, N; Parfait, B; et al.
Abstract : Objective: Germline loss-of-function mutations in the SPRED1 gene have recently been identified in patients fulfilling the National Institutes of Health (NIH) diagnostic criteria for neurofibromatosis type 1 (NF1) but with no NF1 (neurofibromin 1) mutation found, suggesting a neurofibromatosis type 1-like syndrome. Methods: 61 index cases with NF1 clinical diagnosis but no identifiable NF1 mutation were screened for SPRED1 mutation. Results: We describe one known SPRED1 mutation (c.190C>T leading to p.Arg64Stop) and four novel mutations (c.637C>T leading to p.Gln213Stop, c.2T>C leading to p.Met1Thr, c.46C>T leading to p.Arg16Stop, and c.1048_1060del leading to p.Gly350fs) in five French families. Their NF1-like phenotype was characterised by a high prevalence of café-au-lait spots, freckling, learning disability, and an absence of neurofibromas and Lisch nodules in agreement with the original description. However, we did not observe Noonan-like dysmorphy. It is noteworthy that one patient with the p.Arg16Stop mutation developed a monoblastic acute leukaemia. Conclusions: In our series, SPRED1 mutations occurred with a prevalence of 0.5% in NF1 patients and in 5% of NF1 patients displaying an NF1-like phenotype. SPRED1 mutated patients did not display any specific dermatologic features that were not present in NF1 patients, except for the absence of neurofibromas that seem to be a specific clinical feature of NF1. The exact phenotypic spectrum and the putative complications of this NF1 overlapping syndrome, in particular haematological malignancies, remain to be further characterised. NIH diagnostic criteria for NF1 must be revised in view of this newly characterised Legius syndrome in order to establish a specific genetic counselling.